Size-amplified acoustofluidic separation of circulating tumor cells with removable microbeads. Issue 2 (14th May 2018) - Liu, Huiqin; Ao, Zheng; Cai, Bo; Shu, Xi; Chen, Keke; Rao, Lang; Luo, Changliang; Wang, Fu-Bin; Liu, Wei; Bondesson, Maria; Guo, Shishang; Guo, Feng
Abstract: Isolation and analysis of rare circulating tumor cells (CTCs) is of great interest in cancer diagnosis, prognosis, and treatment efficacy evaluation. Acoustofluidic cell separation becomes an attractive method due to its contactless, noninvasive, simple, and versatile features. However, the indistinctive physical difference between CTCs and normal blood cells limits the purity of CTCs using current acoustic methods. Herein, we demonstrate a size-amplified acoustic separation and release of CTCs with removable microbeads. CTCs selectively bound to size-amplifiers (40 μ m-diameter anti-EpCAM/gelatin-coated SiO2 microbeads) have significant physical differences (size and mechanics) compared to normal blood cells, resulting in an amplification of acoustic radiation force approximately a hundredfold over that of bare CTCs or normal blood cells. Therefore, CTCs can be efficiently sorted out with size-amplifiers in a traveling surface acoustic wave microfluidic device and released from size-amplifiers by enzymatic degradation for further purification or downstream analysis. We demonstrate a cell separation from blood samples with a total efficiency ( E total ) of ∼ 77%, purity ( P) of ∼ 96%, and viability ( V ) of ∼83% after releasing cells from size-amplifiers. Our method substantially improves the emerging application of rare cell purification for translational medicine.